Does book genre matter? Boys' and girls' word learning from narrative and informational books in the preschool years. (22nd November 2018) - Bergman Deitcher, Deborah; Johnson, Helen; Aram, Dorit
Abstract : Background: The current study aims to address whether boys and girls learn words differently from shared reading of informational books, which are often perceived as 'boys' books'. Methods: Forty‐five mother‐child dyads (Mean age = 60.4 months, SD  = 6.84) were video recorded reading sets of informational and narrative trade books at home. Children's learning of 12 target words of varying difficulty from each book was tested, controlling for initial vocabulary levels. Results: Boys and girls learned target words from a single reading of both book genres, with no significant differences between the genders. However, gender and genre interacted with girls less likely to learn new words at the expressive level from the informational books. Conclusions: Book genre seems to matter for preschoolers learning new vocabulary at the expressive level from shared reading, with girls at a possible disadvantage. Because of this, additional support, such as direct explanation of words, can be added when reading these books. Highlights: What is already known about this topic : Extensive research supports the use of shared book reading for promoting children's vocabulary learning. Adults (parents and teachers) prefer using narrative books for shared book reading with young children. It is not clear whether differences exist between boys' and girls' learning of words from narrative and informational books. What this paper adds : This paper quantitatively explored whether differences exist between boys' and girls' learning of new vocabulary from shared reading of narratives and informational books. Results found no significant differences between genders in terms of word learning. Gender and book genre did interact in predicting word learning, with boys having an advantage in learning new words at the expressive level from informational books Implications for theory, policy or practice : Informational books have the potential to promote children's word learning. Attempts should be made to counter the perception that informational books are 'boys' books'. Earlier exposure to informational books can be encouraged by including them in shared reading repertoires, along with support for new word learning, such as by direct explanation of vocabulary.